PELAKSANAAN ASUHAN KEPERAWATAN DALAM MENINGKATKAN MUTU PELAYANAN KEPERAWATAN DI PUSKESMAS WOTU KABUPATEN UWU TIMUR - Armawati Abidin (Stikes Graha Edukasi Makassar, 2019)
Objective: To determine the implementation of nursing care in improving the quality of nursing services at Wotu Health Center, East Luwu Regency. Method: This study is an analytic survey with a type of correlational study. The approach used in this study is a cross sectional approach, with the number of respondents as many as 25 people, and sampling using accidental sampling technique. Data collection uses questionnaires and data processing using the SPSS 22.0 program which is presented in the form of tables and narratives. The analysis carried out was univariate and bivariate with a significance level of ? = 0.05. Results: The results of the study show that nursing services with the implementation of the appropriate health insurance procedures run well and their achievements are on average 87%, assessment, diagnosis, planning and implementation show very good results, that is, an average of 88.0%, while evaluation of work results service only reached 80.0%. Discussion: Nursing is a science that studies the fulfillment of basic human needs ranging from biological, psychological, social and spiritual. Fulfilling these basic needs is applied in the provision of nursing care in professional nursing practice. Nursing is based on a very broad theory. Conclusion: In general, the work ability of nurses in the application of Nursing Standards (SAK) in the form of assessment, diagnosis, planning, implementation and evaluation shows excellent work results. The quality of the implementation of nursing services in the implementation of Nursing Standards (SAK) is carried out with good quality work. Suggestion: For the hospital in this case the Head of the Room and other health personnel related to the management of nursing care can provide training, evaluation tools and maintain in improving the performance of nurses as well as input for management or agency leaders to maintain and improve nurse performance